The Relationship between Students' Perceptions about the Teaching Method of Physics Teachers and Student Learning Interests - Amilit Diatul Ikma; Herman Nirwana (Universitas Negeri Padang, 2019)
This study aims to describe students' perceptions of the teaching methods of teachers and describe students' interest in learning and examine the relationship between students' perceptions of the teaching methods of teachers with student learning interests. This research is a quantitative research with correlational descriptive research type. The research variables consist of two, namely: students' perceptions of the teaching methods of teachers (X) are independent variables and interest in learning (Y) are dependent variables. The study population was all students of SMPN 3 Sungai Geringging Pariaman in the 2018/2019 school year with a sampling technique using proportional stratified random sampling. The type of data used in this study is interval data with primary data sources. The instrument used in this study was in the form of scale. The shape of the scale used is the Likert scale model. The results found that the average teaching method of teachers in general was in the medium category, and most students at SMPN 3 Sungai Geringging had an interest in learning in the medium category. The average student learning interest in general is also in the quite good category, and the teaching methods of teachers at Sungai Geringging 3 Junior High School are quite good. The better the condition of the school environment, the higher the concentration of student learning, and vice versa the less good the condition of the school environment, the lower the concentration of student learning.